Immune checkpoint inhibitors as potential therapy for reverting T-cell exhaustion and reverting HIV latency in people living with HIV - Benito, José M.; Restrepo, Clara; García-Foncillas, Jesús; Rallón, Norma (Frontiers in Immunology, 2023)
The immune system of people living with HIV (PLWH) is persistently exposed to antigens leading to systemic inflammation, despite combination antiretroviral treatment (cART). This inflammatory milieu promotes T-cell activation and exhaustion. Furthermore, it produces diminished effector functions including loss of cytokine production, cytotoxicity, and proliferation, leading to disease progression. Exhausted T-cells show overexpression of immune checkpoint molecules (ICs) on the cell surface, including programmed cell death protein 1 (PD-1), cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), T-cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT), and lymphocyte activation gene-3 (LAG-3). The ICs also play a crucial role in T-cell exhaustion by reducing the immune response to cancer antigens. Immunotherapy based on immune checkpoint inhibitors (ICIs) has changed the management of a diversity of cancers. Additionally, the interest in exploring this approach in the setting of HIV infection has increased, including AIDS-defining cancers and non-AIDS-defining cancers in PLWH. To date, research on this topic suggests that ICI-based therapies in PLWH could be a safe and effective approach. In this review, we provide an overview of the current literature on the potential role of ICI-based immunotherapy not only in cancer remission in PLWH but also as a therapeutic intervention to restore immune response against HIV, revert HIV latency, and attain a functional cure for HIV infection.